Enhanced CpG Mutability and Tumorigenesis in MBD4-Deficient Mice - Millar, Catherine B; Guy, Jacky; Sansom, Owen J; Selfridge, Jim; MacDougall, Eilidh; Hendrich, Brian; Keightley, Peter D; Bishop, Stefan M; Clarke, Alan R; Bird, Adrian P (AMER ASSOC ADVANCEMENT SCIENCE, WASHINGTON, 2002)
The mammalian protein MBD4 contains a methyl-CpG binding domain and can enzymatically remove thymine (T) or uracil (U) from a mismatched CpG site in vitro. These properties suggest that MBD4 might function in vivo to minimize the mutability of 5-methylcytosine by removing its deamination product from DNA. We tested this hypothesis by analyzing Mbd4(-/-) mice and found that the frequency of of C 3 T transitions at CpG sites was increased by a factor of three. On a cancer-susceptible Apc(Min/+) background, Mbd4(-/-) mice showed accelerated tumor formation with CpG --> TpG mutations in the Apc gene. Thus MBD4 suppresses CpG mutability and tumorigenesis in vivo.